INTESTINAL MICROBIOTA AS A KEY LINK IN THE FORMATION OF IMMUNITY AND MENTAL HEALTH OF A PERSON IN THE CONTEXT OF SCIENTIFIC AND TECHNOLOGICAL EVOLUTION OF SOCIETY - Azamatov R.A. (Uzbekistan Open Conference, 2025)
The article examines the interconnection between gut microbiota, the immune system, and human mental health in the context of rapid scientific and technological evolution. It demonstrates how technological development, urbanization, dietary changes, and chronic stress affect the composition and function of the intestinal microbiota. These shifts influence both immune and neural regulation, creating new challenges for human health in the 21st century. The paper also discusses sociocultural aspects of human–microbiome interaction in the age of digitalization and environmental change.
Keywords: gut microbiota; immunity; mental health; technological progress; t–brain–immune axis; urbanization